Gut, dass wir einmal die hot potatoes ausgraben: Briefwechsel mit Theodor W. Adorno, Ernst Bloch, Max Horkheimer, Herbert Marcuse und Helmuth Plessner - Anders, Günther (2022)
This volume contains the previously unpublished correspondence of the philosopher and writer Günther Anders (1902-1992) with philosophers of a related philosophical tradition. Some of the letters date from the pre-war period of the 1920s and 1930s, the majority dates from the post-war period up to the 1970s. Based on the correspondence of this volume, Anders' intellectual and biographical development from an academic philosopher to a politically engaged thinker and activist can be traced. Moreover these letters make it clear that he was part of an intellectual network that included numerous philosophers, writers and activists of the 20th century and therefore are also a contemporary historical document which illustrates a part of German history of philosophy of the 20th century.